Antitoxin activity of Mimosa pudica root extracts against Naja naja and Bangarus caerulus venoms - Subramani Meenatchisundaram, Selvin Priyagrace, Ramasamy Vijayaraghavan, Ambikapathi Velmurugan, Govindarajan Parameswari, Antonysamy Michael (Bangladesh Pharmacological Society, 2009)
Aqueous extract of dried roots of Mimosa pudica was tested for inhibitory activity on lethality, phospholipase activity, edema forming activity, fibrinolytic activity and hemorrhagic activity of Naja naja and Bangarus caerulus venoms. The aqueous extract displayed a significant inhibitory effect on the lethality, phospholipase activity, edema forming activity, fibrinolytic activity and hemorrhagic activity. About 0.14 mg and 0.16 mg of M. pudica extracts were able to completely neutralize the lethal activity of 2LD50 of Naja naja and Bangarus caerulus venoms respectively. The present finding suggests that aqueous extract of M. pudica root possesses compounds, which inhibit the activity of Naja naja and Bangarus caerulus venoms.